2022
DOI: 10.1007/s10533-022-00945-5
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for sources of dissolved carbon and the role of organic matter respiration in the Fraser River basin, Canada

Abstract: Sources of dissolved and particulate carbon to the Fraser River system vary significantly in space and time. Tributaries in the northern interior of the basin consistently deliver higher concentrations of dissolved organic carbon (DOC) to the main stem than other tributaries. Based on samples collected near the Fraser River mouth throughout 2013, the radiocarbon age of DOC exported from the Fraser River does not change significantly across seasons despite a spike in DOC concentration during the freshet, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The multi-catchment research of Williamson et al (2021) 2021) tackles a major river basin, the Mississippi, USA, using optical and molecular-scale approaches to reveal the impacts of anthropogenic land cover on DOC flux and the molecular composition of the stream DOM pool, with many parallels to be drawn between this study and the DOC findings reported by Yates et al (2022) and Williamson et al (2021). Voss et al (2022) then use a suite of molecular and isotope chemistry approaches to infer the likely sources of DOC and the role of organic matter respiration on stream DOM pool composition in another large river basin: the Fraser River, in SW Canada. In this work they demonstrate the close coupling between DOC and DIC, with around a third of DIC deriving from DOC respiration, confirming the active biogeochemical processing of C in the river, and the importance of the DOM pool in this cycle.…”
Section: Exploring New Dimensions In the Diagnosis Of Ecosystem Respo...mentioning
confidence: 96%
“…The multi-catchment research of Williamson et al (2021) 2021) tackles a major river basin, the Mississippi, USA, using optical and molecular-scale approaches to reveal the impacts of anthropogenic land cover on DOC flux and the molecular composition of the stream DOM pool, with many parallels to be drawn between this study and the DOC findings reported by Yates et al (2022) and Williamson et al (2021). Voss et al (2022) then use a suite of molecular and isotope chemistry approaches to infer the likely sources of DOC and the role of organic matter respiration on stream DOM pool composition in another large river basin: the Fraser River, in SW Canada. In this work they demonstrate the close coupling between DOC and DIC, with around a third of DIC deriving from DOC respiration, confirming the active biogeochemical processing of C in the river, and the importance of the DOM pool in this cycle.…”
Section: Exploring New Dimensions In the Diagnosis Of Ecosystem Respo...mentioning
confidence: 96%